Detoxifying the heavy metals: a multipronged study of tolerance strategies against heavy metals toxicity in plants - Ejaz, Ujala; Khan, Shujaul Mulk; Khalid, Noreen; Ahmad, Zeeshan; Jehangir, Sadia; Fatima Rizvi, Zarrin; Lho, Linda Heejung; Han, Heesup; Raposo, António (Frontiers in Plant Science, 2023)
Heavy metal concentrations that exceed the permissible limits seriously threaten human life, plant life, and other life forms. Toxic heavy metals are emitted in the soil, air, and water by different natural and anthropogenic activities. Plants consume toxic heavy metals from their roots and foliar part, which are inside the plant, and heavy metals may interfere with various aspects of the plants, such as biochemistry, bio-molecules, and physiological processes, which usually translate into morphological and anatomical changes. They use various strategies in order to deal with the toxic effects of heavy metal contamination. Some of these strategies include the restriction of heavy metals to the cell wall, vascular sequestration, and synthesis of various biochemical compounds, such as phyto-chelators and organic acids in order to bind the free moving heavy metal ions so that the toxic effects are minimized. This review focuses on several aspects of genetics, molecular, and cell signaling levels, which integrate in order to produce a coordinated response to heavy metal toxicity as well as interpret the exact strategies behind the tolerance of heavy metals stress. It is suggested that various aspects of some model plant species must be thoroughly studied in regards to comprehending the approaches of heavy metal tolerance in order to put that knowledge into practical use.